SWOT ANALYSIS OF THE RURAL TOURISM AS A CHANNEL OF MARKETING FOR AGRICULTURAL PRODUCTS IN SERBIA - Krasavac Chroneos, Biljana; Katica, Radosavljevic; Bradic-Martinovic, Aleksandra (Economics of Agriculture, 2018)
In many countries, rural areas are undergoing significant socio-demographic and economic changes, and this trend is also present in Serbia. From the economic and demographic point of view, and this is particularly true for southern Serbia, the problem of depopulation, ageing and extinction of the village has arisen. The subject of this paper is rural tourism in Serbia, which is observed in the context of the new channel for marketing agricultural products of rural households and analyzed by SWOT methodology in order to capture all strengths, weaknesses, opportunities and possible threats. Results show that one of the highest priorities is the synthesis of agriculture and tourism in Serbia, which would be the basis for the development of diversification in rural communities. The development and advancement of the rural environment represent a sustainable and stable regional economic development.